2017
DOI: 10.17533/udea.ikala.v22n01a02
|View full text |Cite
|
Sign up to set email alerts
|

Direct vs. Indirect Written Corrective Feedback: Student Perceptions

Abstract: Studies have shown that most teachers give written corrective feedback to written work in ELT, and that students wish to receive it. However, the debate regarding which type of feedback may be more effective is far from settled. This study reports on action research carried out with intermediate learners in a Chilean university. The teacher/researcher changed from providing direct to indirect, coded feedback and explored the responses of six learners to the two types of feedback. The data collected point to ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 41 publications
4
56
1
2
Order By: Relevance
“…In addition, more studies have been performed to investigate the effectiveness of WCF in developing learners' accuracy in L2 development that followed research designs like the ones used in investigating various forms of oral corrective feedback (CF). A consistent evidence provided by these recent studies (Sheen, 2007(Sheen, , 2010Bitchener, 2008;Ellis et al, 2008;Sheen, Wright, & Moldawa, 2009;Bitchener & Knoch, 2009a, 2009bVan Beuningen, de Jong, & Kuiken, 2012;Shintani, Ellis, & Suzuki, 2014;Stefanou & Revesz, 2015;Karim & Nassaji 2018 ;Westmacott, 2017;Banaruee, Khatin-Zadeh, Ruegg, 2018) revealed that CF has performed a significant role in assisting learners to acquire grammatical features thus improving their linguistic proficiency in the target structure of the language.…”
Section: Introductionsupporting
confidence: 70%
“…In addition, more studies have been performed to investigate the effectiveness of WCF in developing learners' accuracy in L2 development that followed research designs like the ones used in investigating various forms of oral corrective feedback (CF). A consistent evidence provided by these recent studies (Sheen, 2007(Sheen, , 2010Bitchener, 2008;Ellis et al, 2008;Sheen, Wright, & Moldawa, 2009;Bitchener & Knoch, 2009a, 2009bVan Beuningen, de Jong, & Kuiken, 2012;Shintani, Ellis, & Suzuki, 2014;Stefanou & Revesz, 2015;Karim & Nassaji 2018 ;Westmacott, 2017;Banaruee, Khatin-Zadeh, Ruegg, 2018) revealed that CF has performed a significant role in assisting learners to acquire grammatical features thus improving their linguistic proficiency in the target structure of the language.…”
Section: Introductionsupporting
confidence: 70%
“…First, EFL learners had a strong interest in teacher comments, appreciated the feedback, and misinterpreted some teacher feedback comments (Amara, 2015). The study has significantly developed knowledge of learners' perceptions, most students in this L2 class stated indirect feedback was more helpful and it was proved that it might also help strengthened grammar skills and motivate self-learning behavior (Westmacott, 2017). Furthermore, Mahfoodh & Pandian (2011) suggested that students perceived their teachers' written feedback as useful, very crucial for language accuracy.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Therefore, it is necessary to review the learners' perception on teacher direct written corrective feedback in order to have further knowledge on the implementation of direct teacher corrective feedback. Studies on perception have been conducted (Amara, 2015;Westmacott, 2017;Mahfoodh & Pandian, 2011;Erkkilä, 2013;Tangkiengsirisin & Kalra, 2016;and Chung, 2015). First, EFL learners had a strong interest in teacher comments, appreciated the feedback, and misinterpreted some teacher feedback comments (Amara, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study revealed that participants was strongly motivated with teacher comments. Second, a study conducted by (Westmacott, 2017) about direct vs. indirect written corrective feedback on the student perceive. The study revealed that many language learners stated that indirect feedback was more helpful.…”
Section: Related Workmentioning
confidence: 99%